The impact of M&A on technology sourcing strategies - Elena Cefis (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
The paper investigates the effects of Mergers and Acquisitions (M&A) on corporate research and development (R&D) strategies using Community Innovation Survey (CIS) data on the Dutch manufacturing sector. The focus of the research is whether M&A affect corporate innovation strategies, favouring in-house R&D and innovation expenses versus external technological sourcing. The results show that M&A activities have a positive and significant impact on innovation investments by firms, and particularly on R&D intensity and total expenditure on innovation. M&A affect corporate innovation strategies, favouring in-house R&D versus external technological sourcing. Firm postmerger behaviour favours the consolidation of the knowledge, competences and capabilities that have been acquired by merging with or by buying another firm, confirming that the reasons for a merger or acquisition are most often related to firms' innovative performance. Following involvement in a M&A, firms tend primarily to focus on fully integration of their resource bases in order to enable them to produce and sell innovative products that are new to the market.
Keywords: D21; O31; O32; L22; 330; Technology sourcing; innovation; M&A; Heckman two-stage; Bi-Tobit